Bioassay-Guided Isolation and Structure Elucidation of Bioactive Phytoconstituents with Inhibitory Activity against Carbohydrate-Hydrolyzing Enzymes from the Aerial Parts of Premna odorata Blanco - Mendoza, Ronel Abad; Shen, Chien-Chang; Tsai, Po-Wei; De Castro-Cruz, Kathlia Aguila (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: This study aimed to isolate the bioactive components from the aerial parts of Premna odorata Blanco and to evaluate the hypoglycemic potentials of the crude extracts, sub-fractions and final isolate. Materials and Methods: The plant material underwent a series of enzyme assay-guided isolation and purification having the fractions assayed for inhibitory activity against α-amylase using 3,5-dinitrosalicylic acid (DNS) colorimetric method for each stage. H.1 isolate was tested for α-amylase and α-glucosidase inhibitory activity and glucose uptake by yeast cells. Phytochemical characterization and 1H and 13C NMR spectral analysis were done for the structure elucidation of H.1. Results: In vitro amylase studies revealed that at 100 μg/mL concentrations, hexane crude extract, fraction F (20%/80% and 10%/90% n-hexane/dichloromethane fractions) and F.3 (10:1 v/v petroleum ether/ethyl acetate sub-fraction) exhibited 34.38±0.116%, 71.86± 4.909% and 42.16±1.257% inhibition against α-amylase (at 1000 μg/mL concentration), respectively. H.1 isolate exerted significant inhibition (p < 0.05) of 55.99± 2.202% and 72.43±3.988% against α-amylase and α-glucosidase enzyme (both at 1000 μg/ mL concentration), respectively and significant glucose uptake of 13.85± 0.368%. The purified isolate was spectroscopically confirmed as a 5:1 mixture of β- sitosterol (H.1a) and stigmasterol (H.1b). Conclusion: The compounds have significant inhibitory activity against carbohydrate-hydrolyzing enzymes and may be potentially developed as adjuvant pharmacotherapy for type 2 diabetes.
Keywords: Premna odorata; α-amylase; α-glucosidase; Bioassay; Hyperglycemia; Inhibition